Test pattern generation and partial-scan methodology for an asynchronous SoC interconnect. - Efthymiou, A. (IEEE Transactions on VLSI systems)
Asynchronous design offers a solution to the interconnect problems faced by system-on-chip (SoC) designers, but their adoption has been held back by a lack of methodology and support for post-fabrication testing. This paper first addresses the problem of testing C-elements, an important building block of asynchronous circuits. A simple method for generating test patterns is described which is shown to be applicable for a wide range of implementations. Based on the C-element testability, a partial scan technique was developed that achieves a test coverage of over 99.5% when applied to an asynchronous, network-on-chip, interconnect fabric. Test patterns are automatically generated by a custom program, given the interconnect topology. Area savings of at least 60% are noted, in comparison to standard, asynchronous, full-scan level-sensitive scan devices (LSSD) methods.